Positional differences in the cardiorespiratory, autonomic, and somatic profiles of professional soccer players - Martin Semjon; Michal Botek; Zbyněk Svozil; Andrew J. McKune (Palacký University Olomouc, 2016)
Background: In order to optimize training in soccer, knowledge about the specific position fitness demands and characteristics is required. Objective: The aim of the study was to determine whether there are position specific differences in somatic, cardiorespiratory and autonomic cardiac profiles of professional senior Czech soccer players. Methods: All players (N = 120) were divided into six groups according to field positions: goalkeeper (GK; n = 11), external defenders (ED; n = 15), central defenders (CD; n = 18), external midfielders (EM; n = 18), central midfielders (CM; n = 24) and forwards (F; n = 34). Players underwent anthropometrical and heart rate variability (HRV) assessment, and a maximal incremental running test in order to obtain maximal oxygen uptake (VO2max) and heart rate. HRV variables were transformed using the natural logarithm (Ln). Results: GK and CD were significantly (p = .005) heavier than ED, EM, CM, and F; while F were significantly (p = .026) heavier than CM and EM. GK and CD were significantly (p = .008) taller than ED, EM, CM, F; and EM were significantly (p = .041) shorter than CM and F. The only significant (p = .043) difference in percentage of body fat was observed in CD compared with CM. A significantly (p = .021) lower VO2max was observed for GK compared with ED, CD, EM, CM, and F. Supine HRV was significantly (p = .039) lower for Ln LF/HF in GK compared with F. Standing HRV was significantly (p = .03) lower for Ln LF in CD compared with both ED and F, significantly (p = .028) higher for Ln LF/HF in ED compared with CD and EM. Conclusions: In soccer, specific positions are associated with different height, body mass and aerobic capacity. A lower VO2max and vagal activity in GK compared with other playing positions may not be considered as disadvantage for performance in this specific playing position.